The Impact of QRIS Payment Usage on Business Income Growth in MSMEs - Angelicia; Syarbini Ikhsan; Umiaty Hamzani; Gita Desyana; Djunita Permata Indah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to examine the effect of the implementation of the Quick Response Code Indonesian Standard (QRIS) in increasing business income, especially for Micro, Small and Medium Enterprises (MSMEs) using the Technology Acceptance Model (TAM) approach. The method used in this study is a descriptive quantitative approach, which aims to provide an overview of the QR Code implementation. The population in this study involved MSME owners, with a sample taken from 100 respondents through non-probability sampling techniques. Data collection was done through questionnaires. Data analysis includes testing research instruments to assess data quality (validity and reliability), classical assumption test (normality), as well as multiple linear regression analysis and hypothesis testing (t test and F test). The results show that QRIS implementation and user satisfaction have a significant influence on increasing MSME income, which supports TAM theory regarding the importance of perceived usefulness and perceived ease of use in technology acceptance. However, other variables, such as QRIS usage literacy, convenience of use, and QRIS service price, did not show a significant influence on MSME income. Simultaneously, these factors still have an effect on MSME income, although with different variations in influence.